Coronary microcirculatory dysfunction after percutaneous coronary intervention: pathogenesis, diagnosis, and therapeutic strategies - BoYuan, Jin; TingTing, Wang; ChengJun, Hua; XinYi, Han; YuShan, Chen (Frontiers in Cardiovascular Medicine, 2025)
Coronary microvascular dysfunction (CMD) can lead to a variety of severe adverse cardiovascular events. CMD represents the primary cause of recurrent angina pectoris following percutaneous coronary intervention (PCI). The etiology of post-PCI CMD is complex and largely occult, which significantly impairs the therapeutic efficacy of PCI. This article reviews the physiological functions of the coronary microcirculation, as well as the latest research progress on the pathogenesis, diagnosis, and treatment of CMD after PCI. Finally, it highlights the scientific issues that urgently need to be addressed regarding CMD after PCI and proposes future research directions, with the aim of providing forward-looking insights for the prevention and treatment of CMD after PCI in the future.